The impact of anastomotic leakage characteristics on the occurrence of anastomotic stenosis after colorectal resection, a retrospective cohort study - Abdelhadi, Schaima; Tzatzarakis, Emmanouil; Hermann, Maike; Orth, Vanessa; Vedder, Katharina; Briscoe, Jannis; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ (International journal of colorectal disease, 2024)
Introduction Anastomotic stenosis (AS) is a common complication after colorectal resection. However, the predisposing factors for stricture formation are not fully understood. Previous studies have shown anastomotic leakage (AL) to be a risk factor for the occurrence of AS. Therefore, we aim to investigate the impact of anastomotic leakage characteristics on the occurrence of anastomotic stenosis after colorectal resection. Methods Consecutive patients with AL following elective, sphincter preserving, colorectal resection, with or without diversion ostomy, between January 2009 and March 2023 were identified from a prospectively collected database. The characteristics of the anastomotic leakage, patient baseline and operative characteristics as well as the postoperative outcomes were analyzed using univariate and multivariate logistic regression to identify factors associated with the occurrence of post-leakage AS. Results A total of 129 patients developed AL and met the inclusion criteria. Among these, 28 (21.7%) patients were diagnosed with post-leakage AS. There was a significantly higher frequency of patients with neoadjuvant radiotherapy (18% vs 3%; p = .026) and hand-sewn anastomoses (39% vs 17%; p = .011) within the AS group. Furthermore, the extent of the anastomotic defect was significantly higher in the AS group compared with the non-AS group (50%, IQR 27-71 vs. 20%, IQR 9-40, p = 0.011). Similar findings were observed between the study groups regarding age, sex, BMI, ASA score, medical comorbidities, diagnosis, surgical procedure, surgical approach (open vs. minimally invasive), and anastomotic fashioning (side-to-end vs. end-to-end). On multivariate analysis, the extent of the anastomotic defect (OR 1.01; 95% CI 1.00-1.03; p = 0.034) and hand-sewn anastomoses (OR 2.68; 95% CI 1.01-6.98; p = 0.043) were confirmed as independent risk factors for post-leakage AS. No correlation could be observed between the occurrence of post-leakage AS and the ISREC grading of AL, the anastomotic height or the management of AL. Time to ostomy reversal was significantly longer in the AS group (202d, IQR 169-275 vs. 318d IQR 192-416, p = 0.014). Conclusion The extent of the anastomotic defect and hand-sewn anastomoses were confirmed as independent risk factors for the occurrence of post-leakage AS. No correlation could be observed between the ISREC grading of AL, the anastomotic height or AL management, and the occurrence of post-leakage AS.